2019
DOI: 10.2337/dc18-2198
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy Habitual Intakes of Total, Supplemental, and Food Folate and Risk of Gestational Diabetes Mellitus: A Prospective Cohort Study

Abstract: To identify novel modifiable risk factors of gestational diabetes mellitus (GDM) by examining the association between prepregnancy habitual folate intake and GDM risk. RESEARCH DESIGN AND METHODS The study included 14,553 women in the Nurses' Health Study II who reported at least one singleton pregnancy between the 1991 and 2001 questionnaires. Prepregnancy intakes of total folate, supplemental folate, and food folate were assessed using a food frequency questionnaire administered every 4 years. Incident GDM w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 40 publications
8
66
0
3
Order By: Relevance
“…Folate is one of the key nutrients for pregnant women for its protective effect in preventing birth defects. Two large studies have assessed the association of periconceptional FAS with subsequent GDM risk ( 11 , 12 ) but with inconsistent findings. While preconception FAS was associated with reduced GDM risk in the Nurses’ Study ( 11 ), opposite findings were found for FAS during early pregnancy in the China-Anhui Birth Cohort ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Folate is one of the key nutrients for pregnant women for its protective effect in preventing birth defects. Two large studies have assessed the association of periconceptional FAS with subsequent GDM risk ( 11 , 12 ) but with inconsistent findings. While preconception FAS was associated with reduced GDM risk in the Nurses’ Study ( 11 ), opposite findings were found for FAS during early pregnancy in the China-Anhui Birth Cohort ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two large studies have assessed the association of periconceptional FAS with subsequent GDM risk ( 11 , 12 ) but with inconsistent findings. While preconception FAS was associated with reduced GDM risk in the Nurses’ Study ( 11 ), opposite findings were found for FAS during early pregnancy in the China-Anhui Birth Cohort ( 12 ). However, due to variations in individual folate metabolism, periconceptional folate status evaluated by FAS via questionnaire cannot directly reflect the folate levels in the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 were cohort [13] [23], one had a case-control design [24] and only one was an interventional randomized controlled trial (RCT) [23]. 8 studies were conducted in China [13] [17] [19]- [24], and only one in USA [25]. All studies were published and written in English.…”
Section: Search Resultsmentioning
confidence: 99%
“…Rates of GDM are rising worldwide and associated with adverse perinatal outcomes and long-term cardiometabolic risk in mothers and their offspring 1. This large prospective cohort study investigates the association between pre-pregnancy habitual folate intake and the risk GDM 2…”
Section: Contextmentioning
confidence: 99%